Designing photoswitches for molecular solar thermal energy storage. Issue 12 (18th March 2015) - Lennartson, Anders; Roffey, Anna; Moth-Poulsen, Kasper
Graphical abstract: Abstract: Solar energy conversion and solar energy storage are key challenges for a future society with limited access to fossil fuels. Certain compounds that undergo light-induced isomerisation to a metastable isomer can be used for storage of solar energy, so-called molecular solar thermal systems. Exposing the compound to sun light will generate a high energy photoisomer that can be stored. When energy is needed, the photoisomer can be catalytically converted back to the parent compound, releasing the excess energy as heat. This Letter gives examples of selected molecular solar thermal systems found in the literature. The focus of the Letter is on examples where molecular design has been used to improve the performance of the molecules, and as such it may serve as an inspiration for future design. The selected examples cover five widely studied systems, notably: anthracenes, stilbenes, azobenzenes, tetracarbonyl-fulvalene-diruthenium compounds and norbornadienes.